2007
DOI: 10.1093/ajcn/86.4.1064
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of estrogen receptor α and mutL homolog 1 in normal colonic mucosa: association with folate and vitamin B-12 status in subjects with and without colorectal neoplasia

Abstract: Serum vitamin B-12 but not folate status may be associated with ERalpha promoter methylation in normal-appearing colorectal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 38 publications
4
42
5
Order By: Relevance
“…However, it should be noted that in a recent study, Kawakami et al (2006) observed age-related increases in CGI methylation for some genes classified as Type C by Toyota et al, which argues against any such rigid classification. In the present study, we observed statistically significant age-related increases in CGI methylation for HPP1, p16, APC, AXIN2, SFRP1, SFRP2, SFRP4, N33 and DKK1, but contrary to previous studies (Issa et al, 1994;Kawakami et al, 2006;Al-Ghnaniem et al, 2007), the CGI methylation of ESR1, MYOD and MLH1 showed no correlation with age in our patients. These findings may be due to analytical differences resulting in different CpGs within each island analysed or may indicate that the rates and sites of CGI methylation differ between populations, perhaps because of genotypic variation (Kawakami et al, 2006) or differing exposure to environmental factors, such as diet (Al-Ghnaniem et al, 2007) or commensal microorganisms.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that in a recent study, Kawakami et al (2006) observed age-related increases in CGI methylation for some genes classified as Type C by Toyota et al, which argues against any such rigid classification. In the present study, we observed statistically significant age-related increases in CGI methylation for HPP1, p16, APC, AXIN2, SFRP1, SFRP2, SFRP4, N33 and DKK1, but contrary to previous studies (Issa et al, 1994;Kawakami et al, 2006;Al-Ghnaniem et al, 2007), the CGI methylation of ESR1, MYOD and MLH1 showed no correlation with age in our patients. These findings may be due to analytical differences resulting in different CpGs within each island analysed or may indicate that the rates and sites of CGI methylation differ between populations, perhaps because of genotypic variation (Kawakami et al, 2006) or differing exposure to environmental factors, such as diet (Al-Ghnaniem et al, 2007) or commensal microorganisms.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the average methylation levels were significantly higher in neoplasia-free subjects compared with cancer patients (Table 2) This observation suggests that epigenetic field changes may include both loss and gain of methylation. Our data for ESR1 contradict those of Al-Ghnaniem et al (2007) who reported that ESR1 was 19% more methylated in the normal mucosa of cancer patients than in those free of disease. The role of WIF1 in the Wnt signalling pathway is poorly understood.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The main focus of our study was in fact the earlier-stage epigenetic alterations in hMLH1 and MGMT, which might be found before the onset of clinically evident colorectal tumorigenesis. Few attempts have been made to characterize epigenetic changes in these genes in tumor-free human colons, and in all of these studies, the analysis was limited to one segment (generally the rectum) (Shen et al, 2005;Ye et al, 2006;Al-Ghnaniem et al, 2007). In contrast, our study was pancolonic in scope and involved systematic, segment-by-segment, quantitative analysis of hMLH1 and MGMT promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The results are mixed. Some have reported no association with pathology, others that patients with polyps have increased methylation within their colorectal field and two recent reports have even suggested an inverse association between the presence of colorectal neoplasia and background mucosal methylation (Ye et al, 2006;Al-Ghnaniem et al, 2007;Belshaw et al, 2008;Horii et al, 2008;Ally et al, 2009;Figueiredo et al, 2009;Menigatti et al, 2009). Reconciling these discrepant results is limited by nonstandardized mucosal sampling, the important confounders of age and region, the use of variable marker panels and techniques and that adenomas may not be an adequate pathological end point when evaluating methylation markers more closely associated with the CIMP pathway.…”
Section: Introductionmentioning
confidence: 99%